Translating Qur'anic vocative sentences into English : a rhetorical study / Nida S. Omar - Omar, Nida S. (2013)
One of the most important challenges is the conveyance of Qur`anic messages to readership through translation. Rhetorical study of Qur`anic vocative sentences is very exciting since discloses a combination of rhetoric with the Qur`anic translation into English. The present study deals with problems of translating rhetorical purposes of vocative sentences in the Glorious Qur`an into English. The objectives are (1) to determine the types of translation methods that are used during the translation of Qur`anic vocative sentences into English (2) to determine the syntactical and grammatical changes that occur in the translation output of the Qur`anic vocative sentences into English (3) to evaluate if the syntactical and grammatical changes in the translation affect the original rhetorical message of vocative sentences in Qur`anic texts and whether the message of the English is affected in terms of context of situation (field, tenor and mode). The study uses a comparative method and employs eclectically some ideas from Newmark (1988) on translation methods, Haegeman (2006) on the X bar theory, Catford (1965) on shifts, Katz and Fodor (1963) on componential analysis (CA) , and finally Halliday and Hasan (1985) on context of situation. The analysis of this study is based on comparing forty Qur`anic vocative sentences collected from the whole Qur`an with the English rendering of Yusuf Ali (2006). The study has revealed the diversity of translation methods used in translating Qur`anic vocative sentences such as semantic translation, literal translation, communicative translation, free translation, literal and faithful translation, and semantic and faithful translation. Further, the study shows that there are syntactical and grammatical shifts result in not conveying the rhetorical message fully, partially or sustaining the message in the target text. Finally, the study also shows that the translation occasionally affects the transference of the rhetorical purpose of vocative sentences partially or fully due to the translation of context.